Analisis Korelasi antara Massa Jenis dan Kuat Tekan Uniaksial pada Batu Andesit di Kecamatan Bagelen, Kabupaten Purworejo, Jawa Tengah - Astika Putri Roshinta, (ReTII, 2022)
In analyzing the mechanical response and instability in rock engineering, both in the geotechnical and geological fields, the rock strength parameter is one of the most important. The compressive strength of these rocks is often discussed together with physical properties which also affect the response to rock engineering activities. Given that the characteristics of rocks in each area must be different, of course the rock hardness values ​​obtained from the literature are not necessarily relevant to the rocks in the area to be researched. This study uses secondary data from laboratory tests of andesite samples in Bagelan District, Purworejo Regency, Central Java. This study aims to analyze the compressive strength and density of andesite rock. The method used in data analysis is descriptive quantitative method. In this method, the data obtained are in the form of numbers which will be processed according to the description formed. As the name implies, the analysis that will be used will use a lot of sentences because it explains the results of the relationship between parameters with the help of a statistical analysis result with the Pearson correlation approach and linear regression graph. The rock material has a density value of 2.05 g/cm3 – 2.72 g/cm3 and a uniaxial compressive strength value ranging from 17.22 MPa – 89.24 MPa. This study produces a Pearson correlation value of 0.568 which is positive. This indicates that the greater the mass value, the greater the compressive strength of the rock, and vice versa.